Antioxidant Potential of Ethanol Extracts from Zingiberaceae Plant Leaves - Maulana, Addrian; Thahar, Aufa Sabrina; Khairan, Khairan (Heca Sentra Analitika, 2025)
The development of disease related to oxidative stress must be addressed immediately. An approach is to identify natural antioxidant compounds in plants commonly used by communities. This study measured the potential antioxidant activity of ethanol extracts from three Zingiberaceae species leaves: ginger (Zingiber officinale var. Amarum), turmeric (Curcuma domestica Val), and temulawak (Curcuma xanthorrhiza). Phytochemical profiling was performed using specific reagents, FT-IR analysis, and GC-MS, while antioxidant activity was evaluated using DPPH and ABTS methods. The result showed the presence of saponins, flavonoids, steroids, alkaloids, tannins, fatty acid derivatives, and phytol. The IC50 values of the extracts, determined using the DPPH method, were found to be 28.75 ppm for ginger, 65.86 ppm for turmeric, and 51.41 ppm for temulawak. Using the ABTS method, the IC50 values were 35.4 ppm for ginger, 75.9 ppm for turmeric, and 58.9 ppm for temulawak. The strongest antioxidant activity of ethanol leaf extracts from Zingiberaceae family was found in ginger leaf extract with the lowest value of IC50. These results provide preliminary evidence that Zingiberaceae leaves, which are less studied compared to their rhizomes, possess notable antioxidant potential. Further studies, including the isolation of active compounds and in vivo evaluation, are required to validate these findings and explore their possible applications in the future.